GenTAC registry report: Gender differences among individuals with genetically triggered thoracic aortic aneurysm and dissection1. Issue 4 (26th February 2013) - Holmes, Kathryn W.; Maslen, Cheryl L.; Kindem, Mark; Kroner, Barbara L.; Song, Howard K.; Ravekes, William; Dietz, H.C.; Weinsaft, Jonathan W.; Roman, Mary J.; Devereux, Richard B.; Pyeritz, Reed E.; Bavaria, Joseph; et al.
Abstract Previous data suggest women are at increased risk of death from aortic dissection. Therefore, we analyzed data from the GenTAC registry, the NIH‐sponsored program that collects information about individuals with genetically triggered thoracic aortic aneurysms and cardiovascular conditions. We performed cross‐sectional analyses in adults with Marfan syndrome (MFS), familial thoracic aortic aneurysm or dissection (FTAAD), bicuspid aortic valve (BAV) with thoracic aortic aneurysm or dissection, and subjects under 50 years of age with thoracic aortic aneurysm or dissection (TAAD <50 years). Women comprised 32% of 1, 449 subjects and were 21% of subjects with BAV, 34% with FTAAD, 22% with TAAD <50 years, and 47% with MFS. Thoracic aortic dissections occurred with equal gender frequency yet women with BAV had more extensive dissections. Aortic size was smaller in women but was similar after controlling for BSA. Age at operation for aortic valve dysfunction, aneurysm or dissection did not differ by gender. Multivariate analysis (adjusting for age, BSA, hypertension, study site, diabetes, and subgroup diagnoses) showed that women had fewer total aortic surgeries (OR = 0.65, P < 0.01) and were less likely to receive angiotensin converting enzyme inhibitors (ACEi; OR = 0.68, P < 0.05). As in BAV, other genetically triggered aortic diseases such as FTAAD and TAAD <50 are more common in males. In women, decreased prevalence of aortic operations and less treatment with ACEi may be due to their smaller absolute aortic diameters. Longitudinal studies are needed to determine if women are at higher risk for adverse events. © 2013 Wiley Periodicals, Inc.